Design and Build: Perception of Project Owners and Contractors on Cost in Java, Indonesia - Antonius W. Djojopranoto; Brad L. Benhart (Civil Engineering Dimension, 2017)
Design-build (DB) is a project delivery that has already been used widely in USA, UK, Singapore and in other countries. However, it is not widely used in Indonesia and there are limited studies available on DB. The purpose of this paper is to quantify project owners’ and contractors’ opinions about the perceived benefits of DB in terms of cost in Java, Indonesia. The quantitative research design using survey study was conducted to evaluate stakeholders’ opinion on the impact of DB on cost. Survey forms with questionnaires were sent to ten project owners and ten contractors. Inferential statistics using t-test was used to compare the perception between them. The result shows that project owners and contractors agree that DB project delivery has some benefits on cost. However, implementation has to be improved in order for DB to be a preferable project delivery option.